PENGUASAAN KETERAMPILAN DAN MOTIVASI KERJA TERHADAP TINGKAT PENDAPATAN IBU RUMAH TANGGA DI DESA MURTIGADING BANTUL - Sudaresti Sudaresti; Yoyon Suryono (Universitas Negeri Yogyakarta, 2015)
This study aims to determine: (1) contribution mastery of skills, (2) the contribution of motivation, and (3) the contribution of the mastery of the skills and motivation to work on the level of income trainee housewife hyacinth small and medium enterprises in the village Lutfi Craft Murtigading Plate II , Sanden, Bantul. This study uses a quantitative approach is correlational. The study population was a housewife trainee hyacinth UKM Lutfi Craft Village Murtigading Plate II, Sanden, Bantul. Collecting data using closed-form questionnaire scale. Data were analyzed using simple linear regression and multiple linear regression. The results showed that there is a positive and significant contribution to the mastery of the skills and motivation to work on the level of income trainee housewife hyacinth small and medium enterprises in the village Lutfi Craft Murtigading Plate II, Sanden, Bantul. The amount of the contribution of the mastery of skills and motivation of 30,4% and 22,6%, and both variables together to contribute to the household income levels mother trainee hyacinth UKM Lutfi Craft Village Murtigading Plate II Sanden, Bantul by 48,3%.